Plcg2M28L Interacts With High Fat/High Sugar Diet to Accelerate Alzheimer’s Disease-Relevant Phenotypes in Mice - Oblak, Adrian L.; Kotredes, Kevin P.; Pandey, Ravi S.; Reagan, Alaina M.; Ingraham, Cynthia; Perkins, Bridget; Lloyd, Christopher; Baker, Deborah; Lin, Peter B.; Soni, Disha M.; Tsai, Andy P.; Persohn, Scott A.; et al. (Frontiers in Aging Neuroscience, 2022)
Obesity is recognized as a significant risk factor for Alzheimer's disease (AD). Studies have supported the notion that obesity accelerates AD-related pathophysiology in mouse models of AD. The majority of studies to date have focused on the use of early-onset AD models. Here we evaluate the impact of genetic risk factors on late-onset AD (LOAD) in mice fed a high fat/high sugar diet. We focused on three mouse models created through the IU/JAX/Pitt MODEL-AD Center, LOAD1, LOAD1.Plcg2M28L and LOAD1.Mthfr677C>T. At 2 months of age, animals were placed on a high fat/high sugar diet (HFD) that induces obesity, or a control diet (CD) that does not, until 12 months of age. Throughout the study, blood was collected to assess cholesterol and glucose. Positron emission tomography/computed tomography (PET/CT) was completed prior to sacrifice to image for glucose utilization and brain perfusion. At the completion of the study, blood and brains were collected for analysis. As expected, animals fed the HFD, regardless of genotype or sex, showed a significant increase in body weight compared to those fed the CD. Glucose and cholesterol increased as a function of HFD as well. Interestingly, LOAD1.Plcg2M28L demonstrated an increase in microglia density as well as alterations in regional brain glucose and perfusion when on a HFD. These changes were not observed in LOAD1 or LOAD1.Mthfr677C>T animals when fed a HFD. Furthermore, LOAD1.Plcg2M28L but not LOAD1.Mthfr677C>T or LOAD1 animals showed transcriptomics correlations to human AD modules. Our results show HFD affects brain health in a genotype-specific manner. Further insight into this process may have significant implications in the development of lifestyle interventions for treatment of AD.